Penerapan Model Product Layout Pada Layout Produksi PD HM Kue Pia - Hanna Friska P Friska P; Kokom Komariah; Dicky Jhoansyah (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to analyze the application of production layouts using product layout models in PD HM Kue Pia Sukabumi Regency. Data analysis methods used are case studies, quantitative and descriptive approaches. The results showed that time management was not optimal in each production line, so that production load imbalances often occurred. Based on the calculation results obtained 6% of time wasted from the production process, due to imbalance production costs. In conclusion, a good product layout will provide efficiency in the production process and production time, which in turn will provide an increase in income, conversely if an imbalance in production costs results in the company not being able to maximize production results that also affect income. Keywords: product layout, production management, production time efficiency